The Transnational Formation of the English Novel: The Case of Madame de Villedieu’s The Annals of Love (1672) - Monterrey, Tomás (Miscelánea: A Journal of English and American Studies, 2025)
In the late 1660s and 1670s, Madame de Villedieu (née Desjardins) made a substantial contribution to the evolution of prose fiction, moving the genre from the heroic romance to the nouvelle in France, and thus in England. Her Annales Galantes (1670), translated as The Annals of Love (1672), is a landmark work within the development of the genre. The twenty-one “amorous adventures” that make up this collection contain an impressive array of characters and psychological portraits of individuals enmeshed in a multiplicity of romantic relationships and situations. Drawing from chronicles and historical records and set in Europe and Asia in periods ranging from the early Middle Ages to the modern era, the author presents these stories as factual accounts through her use of sources and reinforces her narrative authority with calculated digressions and metanarrative commentary. This article examines Villedieu’s innovative experiment in history and narrative technique in the literary context of the transition to the nouvelle (and the novel) in England. It studies the ways in which narration in The Annals abandons the unreliable voices and human-like points of view that characterised the English heroic romances, making use of authorial privilege, literary techniques and discourses associated with truth-telling, such as omniscience, biography and history, while constantly reminding readers of her imaginative reconstruction of the stories.
Keywords: Restoration fiction; Desjardins / Villedieu; nouvelle galante; history; omniscience; literary metanarration